OPTIMUM ALGORITHM OF NAVIGATIONAL INFORMATION PROCESSING IN WATER TRANSPORT MANAGEMENT SYSTEMS - Герасимов, С. В.; Тимочко, О. І.; Тимощук, О. М.; Шевченко, А. П.; Трішин, В. В. (Science-based technologies, 2019)
The paper substantiates that the purpose of navigation system or complex of navigation systems in the management of traffic by water transport is to develop a vector of navigational parameters. Such a vector is formed according to the data of the initial measurements and their processing, and then used later in the systems of traffic control by water transport. The calculation of navigation parameters in such systems is based on the algorithm of operation, which, with the functioning of the system of sensors of the primary information (speed and rate meters, as well as accelerations and angles that set the position of the gyroscopes), provide the necessary navigational parameters in the assumption of the absence of errors in these sensors. Realization of such an algorithm of work provides the necessary accuracy of the navigation signal, the characteristics of which are the actual values of navigation parameters. Influence of errors of the complex of navigation systems on providing of the necessary route of movement of water transport is investigated taking into account multiplicative components of errors. Smoothing of errors of movement of water transport due to the inertia of the sensors of navigation systems is carried out approximately. The algorithm of the system of coordinate determination and the navigation system must be as close as possible to the error-free algorithm of work. For this purpose in the work the theoretical apparatus is considered in relation to the calculation of the optimal algorithm for the processing of navigation information. It is substantiated that the practical solution of the problems of optimal filtration is therefore based on certain simplifications in the formulation of the problem, which, of course, leads to loss of optimality of estimates of navigation parameters and, consequently, to increase the error of their evaluation. The optimal algorithm for processing navigation information is provided to provide the necessary accuracy of determining the position of water transport in the route of movement.